Trends and determinants of low body mass index (BMI) among 750,000 adolescents and women of reproductive age in India (P10-086-19) - Young, Melissa; Nguyen, Phuong Hong; Avula, Rasmi; Tran, Lan Mai; Menon, Purnima (Oxford University Press, 2019)
Low BMI among women and girls has implications for their health and that of the next generation. Yet, little is known about the determinants of low BMI despite the known high burden of undernutrition in India. We aimed to use nationally representative data to examine national and state trends for BMI and to identify the determinants of low BMI among adolescent girls and women.